Correlation of Decreased Serum Pituitary Adenylate Cyclase-Activating Polypeptide and Vasoactive Intestinal Peptide Levels With Non-motor Symptoms in Patients With Parkinson’s Disease - Hu, Shiyu; Huang, Shen; Ma, Jianjun; Li, Dongsheng; Zhao, Zhenxiang; Zheng, Jinhua; Li, Mingjian; Wang, Zhidong; Sun, Wenhua; Shi, Xiaoxue (Frontiers in Aging Neuroscience, 2021)
Objective: Pituitary adenylate-cyclase activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP) are two neuropeptides that exhibit anti-inflammatory and neuroprotective properties, modulating the production of cytokines and chemokines, and the behavior of immune cells. However, the relationship between PACAP and VIP levels and Parkinson’s disease (PD) are not clear. The aim of the current study was to evaluate serum PACAP and VIP levels in PD patients and to analysis the correlation between neuropeptide levels and non-motor symptoms. Methods: In this cross-sectional study, we enrolled 72 patients with idiopathic PD and 71 healthy volunteers. Serum PACAP and VIP levels were measured using an enzyme-linked immunosorbent assay (ELISA) kit. Non-motor symptoms were assessed with the Non-Motor Symptoms Scale (NMSS) for PD, including total and single-item scores. Results: The serum PACAP levels of PD patients were significantly lower than those of healthy controls [(76.02 ± 43.78) pg/ml vs. (154.96 ± 76.54) pg/ml, P < 0.001]; and the serum VIP levels of PD patients were also significantly lower than those of healthy controls [(109.56 ± 15.39) pg/ml vs. (136.46 ± 24.16) pg/ml, P < 0.001]. PACAP levels were inversely correlated only with the score on NMSS item five, assessing Attention/memory (r = −0.276, P < 0.05) and lower serum PACAP levels were detected in the cognitive dysfunction subgroup than in the cognitively intact subgroup [(61.87 ± 32.66) pg/ml vs. (84.51 ± 47.59) pg/ml, P < 0.05]; meanwhile, VIP levels were inversely correlated with the NMSS total score (r = −0.285, P < 0.05) and the single-item scores for item one, assessing Cardiovascular (r = −0.257, P < 0.05) and item three, assessing Mood/cognition (r = −0.373, P < 0.05), and lower serum VIP levels were detected in the anxiety subgroup and depression subgroup than in the non-anxiety subgroup and non-depression subgroup, respectively [(107.45 ± 15.40) pg/ml vs. (116.41 ± 13.67) pg/ml, P < 0.05]; [(104.45 ± 15.26) pg/ml vs. (113.43 ± 14.52) pg/ml, P < 0.05]. Conclusion: The serum PACAP and VIP levels of PD patients were significantly lower than those of healthy controls. The non-motor symptoms significantly negatively correlated with serum PACAP level was cognitive dysfunction, while mood disorder was significantly correlated with serum VIP level.